TRANSFORMASI MODEL PEMBELAJARAN UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI MASA PANDEMI COVID-19 : Studi Kasus Mata Pelajaran Fikih Kelas XI MAN 2 Mojokerto - Isti Muchlisianah; Khoirul Umam; Jumari (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2022)
One of the determining factors for the success of teaching and learning is the right learning model or method. The Covid-19 pandemic has had a significant impact on the education and learning sector. This study aims to describe the phenomenon of the transformation of the fiqh learning model as well as the inhibiting and supporting factors in class XI MAN 2 Mojokerto. The research method uses qualitative research. The data used are primary data and secondary data. The results of the study resulted: The fiqh learning model during the covid-19 pandemic changed into an online learning model. Online fiqh learning is carried out with the help of several digital media such as e-learning, Google Meet, Google Classroom, Whatsapp group, Quizizz, Camtasia studio, and Renderforest as well as the availability of madrasa digital libraries to support maximum learning. The teacher provides materials and assignments through the application. Then students deposit the results of their assignments through the application or via e-mail. The application of this online learning model has supporting and inhibiting factors that must be addressed wisely by all authorized parties, in this case teachers, students, parents, and schools, so that learning objectives are achieved optimally.